For this case, what we are going to do is use the following property: Multiply an equation by a scalar. In this case, the scalar will be: k = -2 We have then that equation 2 will be: k * (4x + y) = k * 1 -2 * (4x + y) = - 2 * 1 -8x-2y = -2 Answer: The property that justifies this manipulation is: Multiply an equation by a scalar.
The answer would be B because 2 cups of chocolate to 5 cups of milk the ratio would be 2:5 and you can't put 5:2 because it's asking the ratio of chocolate milk to chocolate pudding not chocolate pudding to chocolate milk.